Farmer preferences for drought tolerance in hybrid versus inbred rice: Evidence from Bihar, India - Ward, Patrick S.; Ortega, David L.; Spielman, David J.; Singh, Vartika (International Food Policy Research Institute, 2013)
This paper addresses the previously unanswered question of whether the private sector might play a future role in developing similar strains through applications of advanced biotechnology, and whether their research and development efforts would benefit poor and vulnerable farmers in hazard-prone ecosystems. We employ discrete choice experiments to examine farmers’ preferences for DT traits and explore heterogeneity in these preferences using primary data collected in rural Bihar, India. Using different modeling approaches to capture preference heterogeneity, our results show that farmers value the reduction in yield variability offered by DT cultivars but are willing to pay even more for rice seed that offers yield advantages even under normal conditions.